Social inequalities and the rise in violent deaths in Salvador, Bahia State, Brazil: 2000-2006 - Luiz Antonio Chaves Viana; Maria da Conceição Nascimento Costa; Jairnilson Silva Paim; Ligia Maria Vieira-
An ecological study was carried out using information zones as units of analysis in order to assess the evolution of socio-spatial inequalities in mortality due to external causes and homicides in Salvador, Bahia State, Brazil, in 2000 and 2006. The Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística - IBGE) and the City Health Department (Secretaria Municipal de Saúde) provided the data sources, and causes of death were reviewed and reclassified based on reports from the Institute of Legal Medicine (Instituto Médico Legal). The information zones were classified into four social strata according to income and schooling. The ratio between mortality rates (inequality ratio) was calculated and confirmed a rise of 98.5% in the homicide rate. In 2000, the risk of death due to external causes and murders in the stratum with the worst living conditions was respectively 1.40 and 1.94 times greater than in the reference stratum. In 2006 these figures were 2.02 and 2.24. The authors discuss the implications for inter-sectoral public policies, based on evidence from the study's findings.